Geneologi Konsep Wahidiyah di Nusantara: Kajian Pemikiran Syeikh Abdul Hamid - Angga Andar Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to explore the genealogy of the Wahidiyah concept in the Indonesian archipelago by tracing the thoughts and contributions of Sheikh Abdul Hamid, a key figure in the development of Wahidiyah. Wahidiyah is a Sufi order that emphasizes dhikr (remembrance of God) and spiritual practices to achieve closeness to God. Sheikh Abdul Hamid, as the founder and central figure of this order, has made numerous contributions through writings, lectures, and spiritual guidance that have been influential in various circles of Indonesian society. The research method used was a literature review of previous articles and a historical analysis of Sheikh Abdul Hamid's works. The results indicate that the Wahidiyah concept developed rapidly in the Indonesian archipelago thanks to the adaptation and integration of local values ​​with Sheikh Abdul Hamid's Sufi teachings. Furthermore, this study found that Wahidiyah teachings succeeded in creating social and spiritual harmony among its followers, thanks to Sheikh Abdul Hamid's inclusive approach. Sheikh Abdul Hamid's primary contribution lies in his ability to articulate complex Sufi teachings in a practical and relevant way for the everyday lives of the Indonesian people. The genealogy of the Wahidiyah concept explored in this study reveals the dynamics of the teachings' development over time, as well as their impact on the spirituality and sociality of Muslims in the Indonesian archipelago.